2012
DOI: 10.1039/c2cc36391g
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-containing, backbone-rigidified foldamers and macrocycles

Abstract: This Feature Article gives an account for a host of readily available foldamers and macrocycles with well-defined shapes and non-deformable cavities that appeared over the last decade. Efforts to create porous molecular structures have led to the establishment of an effective strategy for enforcing the folding of unnatural aromatic oligoamide strands based on an especially robust three-center (bifurcated) hydrogen-bonding interaction. Based on such a strategy, aromatic oligoamides adopting crescent and helical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 97 publications
0
51
0
2
Order By: Relevance
“…[49] When benzene-1,4-dicarboxylic acid precursors were introduced, the cavities of the macrocycles could be enlarged remarkably. [47] Li and Yuan et al also utilized a similar strategy to prepare a number of aromatic amide macrocycles from different diamines and diacyl chlorides, [50,51] while Huc and Jiang et al reported the synthesis of several aromatic amide macrocycles through the self-coupling of discrete quinoline amino acids. [52,53] Zeng and co-workers systematically studied the selfcoupling of several meta-substituted amino acids under different reaction conditions.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 97%
See 1 more Smart Citation
“…[49] When benzene-1,4-dicarboxylic acid precursors were introduced, the cavities of the macrocycles could be enlarged remarkably. [47] Li and Yuan et al also utilized a similar strategy to prepare a number of aromatic amide macrocycles from different diamines and diacyl chlorides, [50,51] while Huc and Jiang et al reported the synthesis of several aromatic amide macrocycles through the self-coupling of discrete quinoline amino acids. [52,53] Zeng and co-workers systematically studied the selfcoupling of several meta-substituted amino acids under different reaction conditions.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 97%
“…Thus, this family of compact backbones has been widely applied for the construction of macrocyclic systems. [47,48] In 2004, Gong and co-workers reported the one-step synthesis of macrocycles 35a-d in 69-82% yields from the corresponding diamine and diacyl chloride precursors. [49] When benzene-1,4-dicarboxylic acid precursors were introduced, the cavities of the macrocycles could be enlarged remarkably.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 99%
“…The amide bond provides an alternative target for OMC formation because of its easy accessibility and irreversible formation 34b. Early in 1984,34a hexalactam 11 was synthesized in 13 % yield by the amidation of the corresponding triamine and bis(carbonyl chloride).…”
Section: Omcs From Irreversible Bondsmentioning
confidence: 99%
“…As such, mimicking the hydrogen-bond donor patterns of oxyanion holes with simple peptides might be extremely challenging due to the flexibility of the peptide backbone. However,p eptide-type foldamers [4] that bear more rigid subunits [5] might offer better possibilities for folding into oxyanion-hole-typec onformations. Av arietyo fr igid aromatic oligomers composed of, for example, pyridine-2,6-carboxamide, [6] anthranilamide, [7] quinoline, [8] quinoxalene, [9] and other aryl-amide monomers, [10] have been studied sincet he 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Still, only scattered examples of nonpeptidic structures in which amide or ester carbonyl groups act as multiple hydrogen-bond acceptors have previouslyb een described, [11] and foldamersthat bear oxyanion-hole-typestructures have not been systematically studied at all. In the previous examples of oligomers, the emphasis was placed on control of the folding properties, governed mainly by the repeating hydrogen-bond patterns [5][6][7][8][9][10] and aromatic interactions, which were adjusted by varyingt he functionalization of the aromatic rings. [10a] In many cases,t he foldamers also contained an interior cavity of varying size at the center of the fold instead of at ight fold stabilized by multiple interactions.…”
Section: Introductionmentioning
confidence: 99%